Authentic leadership approach for enhancing innovation capability: a theoretical investigation. (2016) - Verma, Pratibha; Rao, M.K.
This paper aims to explore how authentic leadership potentially leads to superior innovation capability by fostering creativity components namely: intrinsic motivation, creativity-relevant skills and domain-relevant skills. The insights drawn from this study make known three patterns of relationships among authentic leadership, creativity and innovation capability and, establish the impact of authentic leadership on innovation capability through components of creativity. Based on these insights, some of the significant implications of the study are that, practitioners can get the knowledge on how to foster creativity components to a great extent through authentic leadership and how to motivate employees towards creative and innovative practices which further boost firm's capability to innovate and, compete in the market. Further implications and future prospects are discussed in detail.